In vitro and in vivo regenerative processes resulting from the effect of experimental samples of synthetic polyvinyl formal based hydrogel implants (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To experimentally examine in vitro and in vivo regenerative processes resulting from the effect of experimental samples of synthetic (poly)vinyl formal (PVF) based hydrogel implants.Material and Methods: Scanning electron microscopy (SEM) analysis; Vero cell culture evaluation of in vitro regenerative processes by the wound-healing assay; evaluation of in vivo regenerative processes in the rabbit ocular and crest tissues resulting from the effect of experimental samples of synthetic PVF based hydrogel implants. Experimental studies of hybrid hydrogels were conducted in 20 Chinchilla rabbits (age, 5–6 months and weight, 2–3 kg) that were maintained and fed under similar conditions.Results: The most active regeneration of the damaged Vero cell monolayer (with a wound closure percentage of 91%) resulted from the effect of the sample of PVF/AuNP (12.06 µg/g) hydrogel, followed by PVF-based hydrogel and PVF-based hydrogel impregnated with poly(N-isopropylacrylamide) (PNIPAM). In an in vivo study of local effects after implantation of PVF/AuNP (12.06 µg/g) hydrogel in the scleral sac, orbital tissue or below the crest intradermally, the rabbits who underwent this implantation exhibited mild edema of postoperative suture site and adjacent conjunctiva which reduced on day 10 and practically disappeared on days 17-19. Histomorphological studies of responses of the rabbit orbital and crest tissue to the hydrogel implant found neither implant resorption nor acute inflammation of the surrounding tissue.Conclusion: Our in vitro and in vivo study of regenerative processes resulting from the effect of experimental samples of synthetic PVF based hydrogel implants demonstrated that PVF/AuNP (12.06 µg/g) hydrogel is highly biocompatible and had promise as an implant material.
Keywords: PVF; hydrogel implants; orbit; regeneration; in vitro; in vivo; biocompatibility; implantation